BISNIS JASA PENYALUR TENAGA KERJA PERSPEKTIF HUKUM EKONOMI SYARIAH - Abdurohman, Dede (Fakultas Syariah, 2018)
Working is an attached part of life series. In Indonesia, some people try to be employed through labor distributor services, known as outsourcing. Indonesian law confirms that Outsourcing activities are protected by the act No. 13 of 2003 concerning Manpower, Decree of the Minister of Manpower and Transmigration of the Republic of Indonesia Number: KEP.101/MEN/VI/2004 concerning Procedures for Licensing of Workers/Labor Service Providers. However, workers joining Outsourcing agent considered themselves unprosperous. They then choose demonstration as a way to express their aspiration. The phenomenon of demonstration of labor in Indonesia usually can be seen every year in May. The issue is usually about the minimum wage which is according to them under the welfare standard and another is about outsourcing abolishment. In this article, the author will focus on Outsourcing agent, its system in Indonesia according to Islamic Economic Law’s perspective? The author thinks it is important to discuss since the labors do the demonstration every year for the same demands. Based descriptif kwalitatif analysis in Islamic business law, the outsourcing company is halal. Goverment can up the minimum wage consider the maslahah.Bekerja merupakan bagian tak terpisah dari rangkaian kehidupan. Di Indonesia, beberapa orang memilih mencari pekerjaan melalui agen penyalur tenaga kerja atau yang disebut outsourcing. Hukum di Indonesia menegaskan bahwa kegiatan outsourcing dilindungi oleh Undang-Undang No. 13 Tahun 2003 tentang Ketenagakerjaan, Keputusan Menteri Tenaga Kerja dan Transmigrasi Republik Indonesia No.: KEP.101/MEN/VI/2004 tentang Tata Cara Perijinan Perusahaan Penyedia Jasa Pekerja/Buruh. Namun, buruh yang terjaring dalam lembaga outsourcing menganggap diri mereka belum sejahtera. Karenanya, mereka memilih demonstrasi untuk mengungkapkan aspirasinya. Fenomena demonstrasi para pekerja di Indonesia dapat disaksikan setiap tahunnya pada bulan Mei. Tuntutan mereka biasanya seputar upah minimum yang menurut mereka di bawah standar kesejahteraan dan penghapusan sistem outsourcing. Dalam artikel ini, penulis fokus pada lembaga outsourcing dan sistemnya di Indonesia menurut perspektif Hukum Ekonomi Syariah. Berdasarkan analisis deskriptif kwalitatif, maka perusahaan outsourcing sah secara hukum dan halal menurut hukum ekonomi syariah. Pemerintah dapat menaikkan upah minimum dengan memperhatikan kemaslahatan.